PENERAPAN MANAJEMEN PETERNAKAN BERBASIS ANIMAL WELFARE UNTUK MENINGKATKAN KESEJAHTERAAN HEWAN DI LABORATORIUM LAPANG FAKULTAS KEDOKTERAN DAN KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA - Yustinus Oswin Primajuni Wuhan; Maria Aega Gelolodo; Korbinianus Feribertus Rinca; Maria Laurenci Fanny Permata Kale; Yohanes Timbun Raja Mangihut Ronael Simarmata (Jurnal Media Tropika, 2026)
Animal welfare is a fundamental aspect of modern livestock management that influences ethics, health, and productivity. The Field Laboratory of the Faculty of Medicine and Veterinary Medicine, Universitas Nusa Cendana, faces challenges regarding the limited supply of fresh forage, particularly during the dry season, which risks compromising animal welfare. This community service program aims to implement animal welfare- based livestock management by integrating corn stalk silage technology to ensure sustainable feed availability. The implementation method consisted of three main stages: (1) identification of animal welfare principle applications, (2) silage production training for students and barn staff, and (3) the provision of forage chopper machines. Results of this community service (PkM) program indicate that students and barn staff are now capable of independent silage production, supported by the use of chopper machines which significantly enhanced operational efficiency. In conclusion, this program successfully integrated feed technology solutions and the downstreaming of forage choppers with animal welfare standards to support sustainable livestock productivity.